Advances in targeted delivery of small interfering RNA using simple bioconjugates - Nielsen, Christoffer; Kjems, Jørgen; Sørensen, Kristine Rothaus; Engelholm, Lars Henning; Behrendt, Niels (Expert opinion on drug delivery, 2014)
Development of drugs based on RNA interference by small interfering RNA (siRNA) has been progressing slowly due to a number of challenges associated with the in vivo behavior of siRNA. A central problem is controlling siRNA delivery to specific cell types. Here, we review existing literature on one type of strategy for solving the issue of cell-specific delivery of siRNA, namely delivering the siRNA as part of simple bioconjugate constructs. This review presents current experience from strategies aimed at targeting siRNA to specific cell types, by associating the siRNA with a targeting moiety, in a simple bioconjugate construct. We discuss the use of different types of targeting moieties, as well as the different conjugation strategies employed for preparing these bioconjugate constructs that deliver the siRNA to target cells. We focus especially on the in-built or passive functionalities associated with each strategy, in order to identify key elements of successful siRNA delivery strategies with potential for further exploration. By evaluating the current literature on this subject, we identify strategies and concepts that are suitable for future studies, to enable the development of highly efficient simple bioconjugates for targeted siRNA delivery with therapeutic application.